2018
DOI: 10.1111/wre.12344
|View full text |Cite
|
Sign up to set email alerts
|

Considering the preferences for nitrogen forms by invasive plants: a case study from a hydroponic culture experiment

Abstract: tance of considering plant N form preference to better understand plant invasions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…5); that is, nitrification is the main mechanism that provides NO 3 − ‐N for M. micrantha growth, with AOA playing a major role in the process. This is consistent with previous findings indicating that M. micrantha prefers NO 3 − ‐N over NH 4 + ‐N (Chen & Chen, 2019). These findings also imply that M. micrantha mainly depends on soil N for its growth, rather than atmospheric N obtained via BNF.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5); that is, nitrification is the main mechanism that provides NO 3 − ‐N for M. micrantha growth, with AOA playing a major role in the process. This is consistent with previous findings indicating that M. micrantha prefers NO 3 − ‐N over NH 4 + ‐N (Chen & Chen, 2019). These findings also imply that M. micrantha mainly depends on soil N for its growth, rather than atmospheric N obtained via BNF.…”
Section: Discussionsupporting
confidence: 93%
“…For example, higher nitrification in M. micrantha rhizospheres may lead to higher leaching, and thus reduce soil N availability. However, M. micrantha prefers NO 3 − ‐N over NH 4 + ‐N and produces more biomass when NO 3 − is the sole N source compared with when NH 4 + or NH 4 NO 3 are the sole sources of N (Chen & Chen, 2019). It follows that NO 3 − ‐N in soil will be preferentially absorbed by M. micrantha for growth, and therefore that the accumulation of soil‐available N will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Plants may plastically change their physiological and morphological traits and biomass production in response to varying light and soil nutrient conditions. For example, the biomass and plant height of invasive plants increased (Huang et al ., ; Chen & Chen, ), and the ratio of root to shoot decreased with increasing soil nutrient availability (Huang et al ., ). Under the condition of low light, the biomass and ratio of root to shoot decreased significantly (Hou et al ., ; Huang et al ., ; Yasin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Bidens alba (formerly B . pilosa L.) is an invasive plant species mainly occurring in the subtropics and tropics; this species is recorded to have an extensive range in central and southern China [ 20 ]. Previous studies have shown that B .…”
Section: Introductionmentioning
confidence: 99%